Issues and challenges in implemeting green building incentives among the construction key players in Malaysia / Nur Anis A. Rahman - A. Rahman, Nur Anis (2016)
Green building has introduced by the Malaysian Green Technology Corporation (MGTC) to make sure the construction in Malaysia is environmental friendly, Green building in Malaysia is still considered as new and it is not being recognize and not being apply effectively in Malaysia’s construction. Due to the situation, MGTC have introduced several incentives as the initiatives to improve the green building development in Malaysia. The purpose of this paper is to study about the issues and challenges in implementing green building incentives among the construction key players in Malaysia. Hence, to explore more about the types of incentives and issue or problem that arises in implementation of green building incentives in Malaysia. Furthermore, for this study the method that have been used in order to achieved the aims and objectives is by using extensive desk study or conceptual method, it is the method that based on the existing material that can be obtained by reviewing paper from the others researchers, articles, journals and through reference library. Besides the other method that being used it is based on the questionnaire survey for the 30 numbers of selective respondents based on the study needs. From the study done, there have three types of incentives that have been introduced by government; it is financial, fiscal, and structural or administrative incentives and the most knowledgeable is structural incentives. Besides, there have several issues and challenges that arise it is green building will lead to the higher in cost of construction, negative perception on the green construction, income tax only for qualifying person, dissatisfaction on the incidental cost, limited sources of workers, lack of strategy to promote green building and lack of awareness that will affect the implementation of green building incentives in Malaysia